PENGARUH LUAS PANEN PADI DAN PENGGUNAAN INTERNET OLEH PETANI TERHADAP PRODUKSI PADI PADA WILAYAH KABUPATEN/KOTA DI PROVINSI JAWA TIMUR - Listikarini, Dian Irsalina (Universitas Galuh, 2023)
East Java is one of the provinces that contributes the largest rice production in Indonesia. The Provincial Government of East Java is committed to realizing self-sufficiency in food by increasing rice production. As an effort to increase the amount of rice production to reduce imports and achieve food self-sufficiency, this study is important to find out what factors affect rice production in East Java. This study aims to identify the effect of rice harvesting area and internet use on farmers against the rice production of district/cities in East Java province. This research using quantitative approach with multiple linear regression analysis using district/city cross-sectional data in East Java province in the period 2018. The result of this study indicate that the paddy harvested area and internet use on farmers have a significant and positive effect on paddy production in the district/cities in East Java province.